2010
DOI: 10.1016/j.jvir.2010.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-A, Matrix Metalloproteinase-1, and Macrophage Migration Inhibition Factor Changes in the Porcine Remnant Kidney Model: Evaluation by Magnetic Resonance Imaging

Abstract: Purpose To determine the expression of vascular endothelial growth factor-A (VEGF-A), macrophage migration inhibition factor (MIF), and matrix metalloproteinase-1 (MMP-1) in the porcine remnant kidney model and quantify renal blood flow and volume using phase contrast magnetic resonance imaging with magnetic resonance angiography (PC MRI/MRA). Material and methods In 23 pigs, the left renal artery was completely embolized using polyvinyl acrylide (PVA) particles and the right kidney partially embolized (remn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…MRI has been used to determine renal artery blood flow (RABF). The method has been used in pigs subjected to the remnant kidney model , as well as in patients with CKD , infants with kidney transplants , and healthy subjects . However, MRI‐based RABF measurements are currently not used in clinical practise, partly because reproducibility is uncertain.…”
mentioning
confidence: 99%
“…MRI has been used to determine renal artery blood flow (RABF). The method has been used in pigs subjected to the remnant kidney model , as well as in patients with CKD , infants with kidney transplants , and healthy subjects . However, MRI‐based RABF measurements are currently not used in clinical practise, partly because reproducibility is uncertain.…”
mentioning
confidence: 99%
“…Interestingly, each of these proteins has been found to be elevated and associated with VNH [9-13,25,26]. We determined the messenger RNA levels for each of these genes using RT-PCR and found that they were all reduced in fibroblast in contact with BOEC compared to fibroblasts alone.…”
Section: Discussionmentioning
confidence: 98%
“…These include increased expression of proteins involved in inflammation, angiogenesis, and extracellular matrix deposition (13, 15, 33, 34). Matrix metalloproteinase (MMPs) are a family of extracellular matrix degrading proteinases.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies, which have demonstrated involvement of VEGF-A in chronic kidney disease, diabetic nephropathy, glomerulosclerosis, and the remnant kidney model (15, 33, 34). Furthermore, inhibiting VEGF-A function using angiostatin has shown to decrease extracellular matrix deposition in the rat remnant kidney model (14).…”
Section: Discussionmentioning
confidence: 99%